Plant-print : A novel method for culturing plant-associated microorganisms - Rahma Ahmed Mohamed Ali Elnemr; Kassem Fouad Elsahhar; Nabil Abrahim Hegazi (Cairo : Rahma Ahmed Mohamed Ali Elnemr, 2019)
High-throughput cultivation methods are recently developed to elucidate the ecology, physiology and biotechnology of the potential missing members of environmental microbiomes. They all apply the concept of 2environmental simulation3 to attain multiple factors that are unknown but necessary to recover microorganisms reluctant for cultivation. Here, we introduce the leaf-based culture media adopting the concept of nature contains all growth factors necessary for microbial growth. Physical pre-treatments of plant leaves, punching, freezing and/or autoclavation, allowed leakage of electrolytes and other nutrients to configure the leaf surface as a natural pad/theatre, similar to in situ environments suitable for the growth of microorganisms requiring specific growth factors, syntrophic partners or interspecific/intraspecific interactions. The prepared incoula of plant, rhizosphere or phyllopsphere, were directly surface-inoculated on top of the prepared leaf surfaces or indirectly passed through membrane filters then placed on the leaf surfaces. The leaf surfaces supported excellent CFUs development very much comparable to standard R2A and plant-teabag culture media. The surface-inoculated leaf method particularly supported better growth of epiphytic and endophytic populations of the phyllosphere. Based on 16S rRNA of the total 122 tested isolates, the plant microbiome of sunflower occupied by 30 species representing Firmicutes, Proteobacteria and Actinobacteria
Thesis (M.Sc.) - Cairo University - Faculty of Agriculture - Department of Microbiology
Issued also as CD
Keywords: Culture medium; Leaf pad; Plant microbiome